2016
DOI: 10.1109/jsac.2016.2577361
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Quality of HTTP Adaptive Streaming Strategies: Cross-Experimental Analysis of Multi-Laboratory and Crowdsourced Subjective Studies

Abstract: Abstract-Today's packet-switched networks are subject to bandwidth fluctuations that cause for degradation of user experience of multimedia services. In order to cope with this problem, HTTP Adaptive Streaming (HAS) has been proposed in recent years as a video delivery solution for the future Internet and being adopted by an increasing number of streaming services such as Netflix and Youtube. HAS enables service providers to improve users' Quality of Experience (QoE) and network resource utilization by adaptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
5
32
0
Order By: Relevance
“…Furthermore, for live streaming receivers, there is the additional metric of live stream latency, which indicates how far is the receiver's playback behind the video source's production progress. It is discussed in [9] that abruptly downgrading video quality during playback would significantly deteriorate QoE. Also, it is shown in [10] that when streaming a monoscopic or stereoscopic 360…”
Section: B Generic Qoe Improvement Techniques Of Http Streamingmentioning
confidence: 99%
“…Furthermore, for live streaming receivers, there is the additional metric of live stream latency, which indicates how far is the receiver's playback behind the video source's production progress. It is discussed in [9] that abruptly downgrading video quality during playback would significantly deteriorate QoE. Also, it is shown in [10] that when streaming a monoscopic or stereoscopic 360…”
Section: B Generic Qoe Improvement Techniques Of Http Streamingmentioning
confidence: 99%
“…It can be found that the achieved rewards of UEs (6-10), incapable of receiving data from the cellular network, are affected by the cellular transmission rate. With a higher cellular transmission rate, the UEs (6-10) can be greatly benefitted from the matured UEs (1)(2)(3)(4)(5). In contrast, the rewards of those UEs will be decreased rapidly.…”
Section: Simulation Results and Analysismentioning
confidence: 99%
“…Each video was encoded with the HM reference software to obtain three bitrate representations or quality levels for each of the frame quality, frame rate, and spatial resolution scaling dimensions respectively. We then chose and adapted the smooth streaming pattern as motivated by Tavakoli et al [28]. Four video sequences ("Spreed", "Bigbuck", "Car" and "Tractor") were selected for this experiment to illustrate the different complexities within different video sequences.…”
Section: Test Conditions and Materialsmentioning
confidence: 99%